Biodegradability and Cytocompatibility of 3D-Printed Mg-Ti Interpenetrating Phase Composites - Yang, Xixiang; Huang, Wanyi; Zhan, Desong; Ren, Dechun; Ji, Haibin; Liu, Zengqian; Wang, Qiang; Zhang, Ning; Zhang, Zhefeng (Frontiers in Bioengineering and Biotechnology, 2022)
Orthopedic hybrid implants combining both titanium (Ti) and magnesium (Mg) have gained wide attraction nowadays. However, it still remains a huge challenge in the fabrication of Mg-Ti composites because of the different temperatures of Ti melting point and pure Mg volatilization point. In this study, we successfully fabricated a new Mg-Ti composite with bi-continuous interpenetrating phase architecture by infiltrating Mg melt into Ti scaffolds, which were prepared by 3D printing and subsequent acid treatment. We attempted to understand the 7-day degradation process of the Mg-Ti composite and examine the different Mg2+ concentration composite impacts on the MC3T3-E1 cells, including toxicity, morphology, apoptosis, and osteogenic activity. CCK-8 results indicated cytotoxicity and absence of the Mg-Ti composite during 7-day degradation. Moreover, the composite significantly improved the morphology, reduced the apoptosis rate, and enhanced the osteogenic activity of MC3T3-E1 cells. The favorable impacts might be attributed to the appropriate Mg2+ concentration of the extracts. The results on varying Mg2+ concentration tests indicated that Mg2+ showed no cell adverse effect under 10-mM concentration. The 8-mM group exhibited the best cell morphology, minimum apoptosis rate, and maximum osteogenic activity. This work may open a new perspective on the development and biomedical applications for Mg-Ti composites.